Functional isocoumarin-containing polymers synthesized by rhodium-catalyzed oxidative polycoupling of aryl diacid and internal diyne. Issue 14 (9th March 2016) - Han, Ting; Deng, Haiqin; Yu, Chris Y. Y.; Gui, Chen; Song, Zhegang; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract : Functional polymers with in situ generated isocoumarin units were constructed facilely by rhodium-catalyzed polymerization of aryl diacid and internal diyne. Abstract : An atom-economical and straightforward polymerization method to generate functional isocoumarin-containing polymers was developed in this work. The oxidative polycoupling of 4, 4′-(1, 2-diphenyl-1, 2-ethenylene)dibenzoic acid and 1, 6-bis[4-(phenylethynyl)phenoxy]hexane proceeds efficiently in dimethylformamide under nitrogen or air in the presence of [Cp*RhCl2 ]2 and a catalytic amount of Cu(OAc)2 ·H2 O at 120 °C for 24 h, generating a polymer with a high molecular weight of up to 42 900 in a high yield of up to 92.9%. An isocoumarin framework forms in situ during the polymerization from readily accessible and inexpensive monomers. The resulting polymer possesses good thermal stability, optical transparency and film-forming ability. Its thin film exhibits high and UV-tunable refractive indices ( n = 1.9697–1.6507) in a wide wavelength region of 390–890 nm. A two-dimensional fluorescent photopattern can be readily fabricated by irradiating its thin film under UV light through a copper mask. Due to the incorporation of tetraphenylethene units in the monomer, the polymer obtained is weakly emissive in solution but it emits intensely when aggregated, demonstrating a phenomenon of aggregation-induced emission.